2015
DOI: 10.1186/s12934-015-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of pathogenic and spoilage bacteria by a novel biofilm-forming Lactobacillus isolate: a potential host for the expression of heterologous proteins

Abstract: BackgroundBacterial biofilms are a preferred mode of growth for many types of microorganisms in their natural environments. The ability of pathogens to integrate within a biofilm is pivotal to their survival. The possibility of biofilm formation in Lactobacillus communities is also important in various industrial and medical settings. Lactobacilli can eliminate the colonization of different pathogenic microorganisms. Alternatively, new opportunities are now arising with the rapidly expanding potential of lacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…On the other hand, experiments on large animals, such as pigs, whose skin has been regarded as the closest surrogate to human skin with regard to similarities in structure and healing, have a disadvantage of extensive costs, handling, and lack of genetic manipulability [131,135]. Certain probiotics have been reported to form robust biofilms in vitro and shown to attach to various host biofilm sites; these include L. casei, L. rhamnosus, L. plantarum, L. reuteri, L. acidophilus, B. bifidum, and B. breve [136][137][138][139][140][141]. Although probiotics form similar biofilm modalities as pathogens, research and evaluation of these biofilms has only occurred in recent years and not necessarily on the skin [43].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, experiments on large animals, such as pigs, whose skin has been regarded as the closest surrogate to human skin with regard to similarities in structure and healing, have a disadvantage of extensive costs, handling, and lack of genetic manipulability [131,135]. Certain probiotics have been reported to form robust biofilms in vitro and shown to attach to various host biofilm sites; these include L. casei, L. rhamnosus, L. plantarum, L. reuteri, L. acidophilus, B. bifidum, and B. breve [136][137][138][139][140][141]. Although probiotics form similar biofilm modalities as pathogens, research and evaluation of these biofilms has only occurred in recent years and not necessarily on the skin [43].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their certification as GRAS (Generally Recognized As Safe) organisms by the US Food and Drug Administration (FDA), the potential of LAB in several applications have been greatly enhanced. LAB have been reported to be utilized as cell factories for the expression of membrane proteins (Douillard et al, 2011), suppression of spoilage and growth of pathogenic bacteria (Jalilsood et al, 2015), production of biocatalyst (Hugenholtz et al, 2000) and delivery of therapeutic substances (Braat et al, 2006;Rottiers et al, 2009). It was suggested that, replacing the attenuated pathogenic bacteria as a delivery vector for therapeutic vaccine with LAB portrays a much safer alternative for cancer treatments (García-Fruitós, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the antimicrobial activity of Lactobacillus was responsible for the expression of heterologous protein. GFP expression was confirmed by the presence of a 27-kDa protein [54]. Another report shows that bacteriocins produced by lactic acid bacteria exert similar characteristics to microsins.…”
Section: Proteinsmentioning
confidence: 63%